Lasting Developmental Effects of Neonatal Fentanyl Exposure in Preweanling Rats - Dora Catré; Maria Francelina Lopes; António Silvério Cabrita (Anesthesiology Research and Practice)
The present study aimed to determine whether neonatal treatment with fentanyl has lasting effects on stressed developing brain. Six-day-old rats were assigned to one of three groups (10 males/group): (1) fentanyl (incision+fentanyl), (2) saline (incision+0.9% saline), and (3) unoperated (unoperated sham). Pups with a plantar paw incision received repetitive subcutaneous injections of fentanyl or vehicle through postnatal days (PNDs) 6 to 8. A nonoperated sham group served as nonstressed control. Studies included assessment of development from PND 6 to PND 21 (growth indices and behavioral testing). Fentanyl administered twice daily for three days after surgical incision had no impact on early growth and development, as measured on PND 9, but showed a lasting impact on later growth, enhanced behavioral development, and lower anxiety, as measured through PNDs 10–21. While this does not completely support a benefit from such treatment, our findings may contribute to support the neonatal use of fentanyl, when indicated, even in premature newborns.